Supratentorial cerebrospinal fluid diversion using image-guided trigonal ventriculostomy during retrosigmoid craniotomy for cerebellopontine angle tumors - Roethlisberger, Michel; Eberhard, Noëmi Elisabeth; Rychen, Jonathan; Al-Zahid, Saif; Jayapalan, Ronie Romelean; Zweifel, Christian; Karuppiah, Ravindran; Waran, Vicknes (Frontiers in Surgery, 2023)
Background Cerebellar contusion, swelling and herniation is frequently encoutered upon durotomy in patients undergoing retrosigmoid craniotomy for cerebellopontine angle (CPA) tumors, despite using standard methods to obtain adequate cerebellar relaxation. Objective The aim of this study is to report an alternative cerebrospinal fluid (CSF)-diversion method using image-guided ipsilateral trigonal ventriculostomy. Methods Single-center retro- and prospective cohort study of n = 62 patients undergoing above-mentioned technique. Prior durotomy, CSF-diversion was performed to the point where the posterior fossa dura was visibly pulsatile. Outcome assessment consisted of the surgeon's intra- and postoperative clinical observations, and postoperative radiological imaging. Results Fifty-two out of n = 62 (84%) cases were eligible for analysis. The surgeons consistently reported successful ventricular puncture and a pulsatile dura prior durotomy without cerebellar contusion, swelling or herniation through the dural incision in n = 51/52 (98%) cases. Forty-nine out of n = 52 (94%) catheters were placed correctly within the first attempt, with the majority of catheter tips (n = 50, 96%) located intraventricularly (grade 1 or 2). In n = 4/52 (8%) patients, postoperative imaging revealed evidence of a ventriculostomy-related hemorrhage (VRH) associated with an intracerebral hemorrhage [n = 2/52 (4%)] or an isolated intraventricular hemorrhage [n = 2/52 (4%)]. However, these hemorrhagic complications were not associated with neurological symptoms, surgical interventions or postoperative hydrocephalus. None of the evaluated patients demonstrated radiological signs of upward transtentorial herniation. Conclusion The method described above efficiently allows CSF-diversion prior durotomy to reduce cerebellar pressure during retrosigmoid approach for CPA tumors. However, there is an inherent risk of subclinical supratentorial hemorrhagic complications.